Mastering ICOFR: Building Effective Internal Control Systems For Compliance And Financial Reporting Accuracy - Yuliastuty Asmara, Rina; Iqbal , Muhammad; Kamil, Islamiah (LPPM Universitas Muhammadiyah Tasikmalaya, 2025)
The GNV Learning Center, acting as the community engagement partner, had difficulties enhancing the participants' competences within the context of implementing Internal Control Over Financial Reporting (ICOFR). Additionally, a significant number of trainees came from businesses that did not have sufficient documentation of their internal controls and had minimal experience recognizing risks or evaluating their effectiveness. In order to address these deficiencies, a community service program with the name